New developments in biomedical engineering - Campolo, Domenico (Croatia : IntechOpen, 2017)
Biomedical Engineering is a highly interdisciplinary and well established discipline spanning across engineering, medicine and biology. A single definition of Biomedical Engineering is hardly unanimously accepted but it is often easier to identify what activities are included in it. This volume collects works on recent advances in Biomedical Engineering and provides a bird-view on a very broad field, ranging from purely theoretical frameworks to clinical applications and from diagnosis to treatment.
Includes bibliographical references.
Keywords: Biomedical & Biomaterials; Biomedical engineering; Medical bioinformatics